Hip Fracture Surgery: Perioperative Outcomes across Different Anesthesia Techniques – A Systematic Review - Sangeetha Chikkegowda; B. Aparna; Malathi Anil Kumar; K Bharath Kumar; Vijayakumar M Heggeri; K. Pushpalatha (Acta Medica International)
Total hip arthroplasty (THA) and total knee arthroplasty (TKA) can benefit from various regional anesthesia (RA) techniques that enhance patient outcomes. Our study aimed to determine if RA reduces mortality, cardiovascular morbidity, deep venous thrombosis (DVT), pulmonary embolism (PE), blood loss, surgery duration, pain, opioid-related side effects, cognitive defects, and hospital stays while improving rehabilitation. A systematic review of randomized controlled trials (RCTs) from 2000 onward compared RA to general anesthesia (GA) and evaluated systemic versus regional analgesia. The evidence from RCTs did not conclusively show that anesthesia type impacts mortality, cardiovascular issues, or DVT and PE incidence with thromboprophylaxis. However, RA may reduce blood loss. Our findings emphasized the importance of individualized analgesic approaches, such as fascia iliaca compartment block, intrathecal morphine, local infiltration analgesia, pericapsular nerve group block, lumbar plexus block, and erector spinae plane block, to optimize pain management and minimize opioid use, highlighting a need for balanced risk–benefit strategies to improve recovery. Surgery duration showed no significant difference between RA and GA. Regional analgesia was more effective in reducing postoperative pain, morphine use, and nausea and vomiting compared to systemic analgesia. Despite these benefits, hospital stay length and rehabilitation outcomes were not significantly influenced by RA or analgesia methods for THA and TKA.